Transhepatic aspiration of the diverticular loop in cephalic duodenum pancreatectomy - Praderi, Raúl; Ormaechea, Carlos; Delgado, Bolívar (Cirugía del Uruguay, 2020)
In cancer of the common bile duct, resection must include cistic duct and the head of the pancreas. Leaking of the jejunal loop after pancreatectomy is prevented by means of a tube in the common bile duct or the cistic duct. When the hile duct stump is nor available, a transhepatic drainage is placed. This technic was used successfully in three cases.